Effects of early enteral and parenteral nutrition support combined with “Internet + nursing service” on quality of life and complications in patients with malignant obstructive jaundice after percutaneous hepatic puncture biliary drainage - Hou, Liping; Li, Huibo; Zhang, Dongyan (Frontiers in Surgery, 2025)
AimWe explored the effects of early enteral and parenteral nutrition support combined with “Internet + nursing service” on quality of life and complications in patients with malignant obstructive jaundice after percutaneous transhepatic choledochus drainage (PTCD).MethodsThe control group (CG) adopted routine nursing and total parenteral nutrition support. The experimental group (EG) adopted “Internet + nursing service” and early enteral + parenteral nutrition support.ResultsCompared with the CG, the EG demonstrated shorter times of first exhaust/first defecation and reduced length of hospital stay. The incidence of complications was lower, and scores for physical, emotional, social, and material life were higher. Nursing satisfaction of patients was better, while self-rating anxiety scale and self-rating depression scale scores were lower. Aminotransferase, total bilirubin, and direct bilirubin levels were reduced, and improvements in CD8+, CD4+, and CD4+/CD8+ levels were more pronounced. By the 7th day of treatment, serum albumin and prealbumin levels were higher in the EG than those in the CG.ConclusionEarly enteral and parenteral nutrition support combined with “Internet + nursing service” can promote the quality of life, improve nutritional status and immune function, and reduce the complications in patients with malignant obstructive jaundice after PTCD.